The Impact of Inquiry Method Usage through Arranging Concept Map for Student Learning Results and Response on Environment Subject in SMA NEGERI 1 Sigli - Tarmizi Tarmizi (Universitas Syiah Kuala, 2014)
The study used quatitative approach with comparative study. The aims were to determine the student achievement and learning response as well as the different of student achievemnt tought by inquiry method with concept maps. The population were students of Class X SMA Negeri 2 Sigli consisting of 227 pupils and the samples were 35 students (experimental-group class) and 35 students (control-group class). Data of teaching learning type was collected throught observation. interview, and field data whereas student achievement collected by design and presentation of concept map, student worksheets, and final test. Data of student response in using the map was collected by questionnaire. The result showed that the value of t-count t-table for student achievement which was 3,45 1,67 indicating the method has affected the student achievement. The mean values of student responses were 3,73 (agree category) for positive qustions and 2,27 (uncentain category) for negative questions. It can be concluded that learning learning process on concept of environment throught inquiry method with concept map has increased student achievement and response of students of SMA Negeri 2 Sigli.